Competencies, Challenges, and Opportunities of Trial Court Stenographers in Rinconada Area, Philippines - Alyssa Florese De Loyola–Lagatic (The Indonesian Institute of Science and Technology Research, 2025)
This study determined the Competencies, Challenges, and Opportunities of Trial Court Stenographers in the Rinconada Area. Specifically, it identified the (1) personal and professional attributes of the Trial Court Stenographers, (2) the competencies of the respondents, (3) the challenges encountered, (4) the coping mechanisms to address varying challenges, and (5) capacity building to enhance the competencies of Trial Court Stenographers in Rinconada Area. Interviews and a survey questionnaire employing a 4 4-point Likert scale were used as the primary data-gathering tool in the study. The data obtained were analyzed using descriptive statistics. Findings revealed that most respondents are female, married, between 50 and 59 years old, and working in the Regional Trial Court (RTC), Judiciary of Iriga City. Results disclosed that Trial Court Stenographers are competent in their respective field of specialization. Trial Court Stenographers encountered varying challenges in the field. Results further state that several coping mechanisms were applied and adopted by Trial Court Stenographers to address relevant challenges in the profession. A capacity building was proposed to enhance the competencies of the Trial Court Stenographers in the Rinconda Area.